Evaluation of teachers of basic education: Political tensions and radical oppositions - Maria de Ibarrola (Arizona State University, 2018)
This paper focuses upon the enactment and implementation of a National Educational Reform in Mexico, which introduced competitive examinations for teachers entering the newly established Professional Teaching Service of the National Educational System, and compulsory evaluation of all teachers in active service for promotion and tenure.  The analysis describes the (1) aims and intentions of the Reform, (2) the force and errors in its implementation, (3) the opposition of a radical wing of the National Union of Educational Workers, and (4) the social turmoil this confrontation has caused.  A theoretical basis for a political analysis of educational reform is provided, one that includes an understanding of the political nature of the reforms, the distinction between design and implementation, and the use of different categories to provide a solid analytical framework.  It is important to understand the actors of the opposing forces, the aims they pursue, the rationale of their arguments, and the nature of their power.